THE PATH FROM THE SERVICE OF GREAT PEOPLE TO A GREAT SCIENTIST, OR THE SERVICES OF THE MUFTI OF MOVAROUNNAHR MUSLIM RELIGIOUS OFFICE, SHEIKH MUKHTARJAN HAJI ABDULLAH, TO THE NATION AND RELIGION - Arslonbekov Nursulton (American Journals, 2023)
"The path from the service of great people to a great scientist, or the services of Sheikh Mukhtarjan Haji Abdullah, mufti of the Movarounnahr Muslim religious office, to the nation and religion." The article talks about the life path of Mukhtarjon Abdullayev, a child of the nation, who was loyal to his homeland and people, and who was a cure for the country's pain during complex political and social crises. The policy of that person in the issue of personnel in the religious office, his activities at international conferences and major events, his foreign trips and the work he carried out for the development of Uzbekistan and inter-ethnic friendship will be highlighted.
Keywords: Islamic ideology, Islam in the Republic of Uzbekistan, foreign trips, personnel policy, scientific conferences, renewed religious office.